Sustainable hybrid G-W filter / Nur Fatin Nasuha Mhd Khatif ... [et al.] - Mhd Khatif, Nur Fatin Nasuha; Ahmad Razan, Fahda Nurhani; Muhamad Bashar, Nur Azwa; Hamzah, Nurakmal (2021)
Abundance of agricultural waste namely rice husk and non-biodegradable glass waste from food industry contributing to the landfilling problem. In addition, burning of the agricultural waste contributing to the air pollution problem. This study provide alternative to the reduction of the abundance of agricultural waste as a filter media in treating greywater namely ablution water. Recycling and treating the greywater solve problem related to water stress issue. This study involves the application of Hybrid Greywater Filter (HGF) in a pilot scale arclic square reactor consist of several layers of filter media; rice husk, sand, glass beads as alternative to crushed glass, and crusher run. The selected water quality parameters namely Turbidity and Chemical Oxygen Demand (COD) were tested in this study. The removal effectiveness for COD and Turbidity are 42% and 14%, respectively. Obtained result show that the Hybrid Greywater Filter is suitable for greywater treatment as it is reducing the selected parameter values. The treated greywater can be used for general usage such as toilet flushing and general cleaning. In addition, the proposed hybrid filter system is essential to be considered as a low-cost greywater treatment system where the usage is waste and low cost materials.